A distinctive ageing: Age and people with intellectual disabilities - José Luis Cuesta Gómez; María Teresa Ortega Camarero; Raquel de la Fuente Anuncibay (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2023)
People with intellectual disabilities have seen their life expectancy increase in recent years to match that of the general population. The aging of each person will depend on the events experienced throughout their lives, their illnesses, and the psychosocial aspects of their environment. In spite of this, in the case of people with intellectual disabilities, there is evidence of a peculiar way of aging, with significant changes with respect to the general population that affect the age of onset of the first symptoms of aging, and physical, emotional, and health status changes. This article performs a systematic review of the literature to demonstrate the peculiarities of aging in people with intellectual disabilities, concluding on the need to know these changes to adequately guide professional care and thus improve their quality of life.